2019
DOI: 10.1177/0976747919852859
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy, Trade Openness and Economic Growth in India Under Monetary-targeting and Multiple-indicator Approach Regimes

Abstract: This article examines the role of monetary policy and trade openness to raise income in India for the monetary-targeting regime and the multiple-indicator approach regime of monetary policy. The impact of the key instruments of monetary policy, namely, money supply, interest rate and exchange rate, with trade openness on income, is assessed. Besides, how interest rate responds to monetary instruments, income and trade openness is studied. Empirical analysis finds a significant positive impact of the broad mone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 31 publications
2
11
0
Order By: Relevance
“…A few studies have done on the openness–growth relation in India. Among these, Hossain and Maitra (2019), for the period 1985–2016, have found a negative impact of trade openness on economic growth particularly in the long run, while in the short run such impact is positive. On the other hand, Sehrawat and Giri (2017) have found a two-way causal relationship between economic growth and trade openness for the period 1982–2014.…”
Section: Review Of Literaturementioning
confidence: 99%
“…A few studies have done on the openness–growth relation in India. Among these, Hossain and Maitra (2019), for the period 1985–2016, have found a negative impact of trade openness on economic growth particularly in the long run, while in the short run such impact is positive. On the other hand, Sehrawat and Giri (2017) have found a two-way causal relationship between economic growth and trade openness for the period 1982–2014.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Our results indicate that it could take about one year (from the year of actual financing) to see the transmission of the impact of IPO financing on economic growth. Combined with the long-run results, our findings suggest that while IPO financing could have some immediate growth-enhancing effects, its overall effects are not significant over the 39 years Suborna Barua | Mahmuda Akter (Hossain & Maitra, 2020). Combining the long-run impacts of BR on EG, we can derive that the actual increases in bank rates and the herding behavior -in combination -raises the interest rates in the market in the long run, which in turn slows down economic growth through a reduced money supply and credit growth as explained earlier.…”
Section: Short-run Impact Of Ipo Financing and Bank Rate On Economic Growthmentioning
confidence: 63%
“…Contractionary measures, such as a higher bank rate could depress the economy by reducing the money supply and loanable funds in the market. Hossain & Maitra (2020) and Tan et al (2020) show a negative long-run impact of real interest rate increases on economic growth.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Ali and Abdullah (2015) noted that the long-run impact of trade openness on economic growth in Pakistan is negative, even though there is evidence of a positive impact only in the short run, due to weak institutions and poor management. The study of Hossain and Maitra (2020) has also revealed that the impacts of trade openness are unstable in the case of India, as trade openness proxies affect economic growth positively in the short-run but negatively in the long-run.…”
Section: Literature Reviewmentioning
confidence: 99%